Pengaruh Pengembangan Keterampilan Dan Pengembangan Karyawan Terhadap Produktivitas Kerja Di Stasiun Gambir PT Kereta Api Indonesia - Salma Salsabila Choirunnisa; Fahmi Susanti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to determine the effect of skills development and employee development on work productivity at Gambir Station of PT Kereta Api Indonesia both partially and simultaneously. This study uses a quantitative method through an associative approach. The sampling technique in this study uses a non- probability sampling technique, namely a saturated sample with a total of 60 respondents taken from all company employees. Data analysis techniques used are: validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, simple & multiple regression test, partial & simultaneous correlation coefficient test, partial & simultaneous determination coefficient test, T test and F test. Based on the results of the multiple linear regression test, the equation Y = 9.149 + 0.118X1 + 0.696X2 is obtained, indicating that the variables of Skills Development and Employee Development have a positive coefficient on the variable Work Productivity. The coefficient of the Skills Development variable gives a value of 0.118, indicating that if the Skills Development variable increases with the assumption that other variables remain constant, the Work Productivity variable will increase. The coefficient of the Employee Development variable is 0.696, indicating that if the Employee Development variable increases, the Work Productivity variable will increase. The correlation value, or R value, of 0.624 and the R-square value of 62.4% indicate a strong relationship between skills development and employee development and work productivity. The F-test also yields a value of 47.327 > 2.770. This indicates that Ho3 is rejected and Ha3 is accepted. Therefore, it can be concluded that skills development and employee development influence work productivity